Digital object rights management: Interoperable client-side DRM middleware - Serrão, C.; Dias, M.; Delgado, J. (Proceedings of the International Conference on Security and Cryptography (SECRYPT 2006), 2006)
In a more and more interconnected world where the available bandwidths are increasing at a pace hard to imagine some time ago, multimedia e-content distribution over digital networks has become one of the biggest available services online. Powered not only by the network high availability but also by the emergence of new compression techniques and digital content consumer device, digital content is gaining momentum. However the same factors that power this emergence are also causing some problems, specially related with the digital content IPR management and protection. These problems are being handled employing DRM - Digital Rights Management technology which lack interoperability. This paper presents and discusses a solution that provides interoperability to DRM-protected content through the employment of a client-side DRM middleware layer. This middleware layer sits at the client-side of a broader DRM system (called DoRM) providing the necessary mechanisms to achieve interoperability between the different digital content rendering applications that the users possesses.